MODEL PEMBELAJARAN PENJASORKES KID’S ATLETIK MELALUI PERMAINAN THE STRENGTH POST PADA SISWA SD KELAS V (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
AbstrakModel pembelajaran penjasorkes Kid’s Atletik melalui permainan The Strength Post adalah suatu metode pembelajaran gerak dasar melompat,berlari dan melempar dengan mengunakan permainan the strenght post pada siswa kelas V SDN 03 Gunungpati,Kecamatan Gunungpati,Kota Semarang tahun 2012. Tujuan penelitian ini untuk menghasilkan model pembelajaran Kid’s atletik dan  meningkatkan daya tahan tubuh melalui permainan The Strength Post pada siswa kelas V SD Negeri 03 Gunungpati dalam pembelajaran penjasorkes sehingga dapat mengembangkan berbagai aspek pembelajaran dan meningkatkan aktivitas jasmani siswa.Data yang diperoleh dari evaluasi ahli diperoleh persentase rata-rata hasil analisis produk sebesar 96% dengan kriteria sangat baik. Oleh karena itu dapat digunakan untuk uji coba kelompok kecil. Data hasil kuesioner siswa pada uji coba kelompok kecil diperoleh rata-rata jawaban dengan  persentase 89,21% dengan kategori baik. Dan data hasil kuesioner siswa uji coba kelompok besar diperoleh jawaban dengan persentase 93,68%. dengan kategori sangat baik. Siswa sudah tidak merasa kesulitan ketika bermain permainan The Strenght Post. Selain itu, setelah melakukan permainan The Strenght Post denyut nadi siswa meningkat . Dalam pembelajaran penjasorkes dibutuhkan pembelajaran yang variatif,inovatif dan tidak membosankan. Bagi guru penjasorkes di sekolah dasar diharapkan dapat menggunakan model permainan The Strenght Post ini dengan efektif.AbstractA model of learning penjasorkes kid athletic game ’ s through the strength post is a method of learning basic jump, motion to run and throw by means of a game the strenght post on the kids class v sdn 03 gunungpati, sub-district gunungpati, the city of semarang 2012. The purpose of this research to produce a model of learning kid’ s athletic and increase the power of lasting the body through the game of the strength post on the kids class v public elementary 03 gunungpati in learning penjasorkes so that it can develop a variety of aspects of learning and increasing the activity of corporeal students. A method of this research is research, development. The procedure product development covering analysis products to be developed, early, developing products experts and revision, validation the trial of a group of small and revision, the trial of large groups and the final product. Collecting data was done using observations on the court and a questionnaire that obtained from the evaluation of the experts and the resultThe data collected from expert evaluation obtained the percentage of average result analysis product of 96 % with criteria very well. Hence can be used to trial smaii group. Data a questionnaire students on trial clusters of small obtained average answer by the percentage 89,21 % with good category. And data a questionnaire students trial large groups obtained answer by the percentage 93,68 %. With category very well. Students have not had a hard when playing the game strenght the post.Besides, after doing game strenght the post the pulse students increase. In learning penjasorkes needed learning variatif, innovative and not boring. For teachers penjasorkes in primary school expected to use the model game strenght the post this effectively.